Kazakh-Chinese relations in the new Silk Road: two strategies – one way (International relations and international law Journal, 2017)
Kazakh-Chinese relations are characterized by long-term «comprehensive strategic partnership». Kazakhstan’s relations with China based on the principle «China – a good neighbor and important partner.» This allows our country to build a stable and peaceful bilateral relations with China based on a more than sixty interstate agreements. Project, technology, investment and other cooperation is based on program strategies and concepts «Nurly Zhol» and «economic belt of the Silk Road.» «Nurly Zhol» is consistent with the concept of «One Belt and One Road». Kazakhstan and the Central Asian countries are in the midst of implementing this megaproeta. The development of transport communications with China declared a priority area.
Keywords: strategic cooperation projects; «Nurly Zhol»; «One belt one way»